2018
DOI: 10.2174/1381612824666180209105625
|View full text |Cite
|
Sign up to set email alerts
|

Selective Antiprotozoal Activity of Nitric Oxide-releasing Chitosan Nanoparticles Against Trypanosoma cruzi: Toxicity and Mechanisms of Action

Abstract: S-nitroso-MSA-CS NPs are promising nanocarriers for the treatment of Chagas's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Biocompatibility, biodegradability and safety of the polymer are essential features to consider when designing PNs. In this sense, the natural polymer CS and its derivatives deserve to be commented as relevant platforms for nanotherapeutic applications, including antimicrobial therapies [ 75 , 76 , 77 ]. CS is classified by the FDA as “generally regarded as safe.” It has been extensively studied in nanotherapeutics and nowadays, there are marketed CS-based formulations in nutraceutical and medical devices [ 44 , 78 ].…”
Section: Polymeric Nanocarriers Against Intracellular Infections: mentioning
confidence: 99%
“…Biocompatibility, biodegradability and safety of the polymer are essential features to consider when designing PNs. In this sense, the natural polymer CS and its derivatives deserve to be commented as relevant platforms for nanotherapeutic applications, including antimicrobial therapies [ 75 , 76 , 77 ]. CS is classified by the FDA as “generally regarded as safe.” It has been extensively studied in nanotherapeutics and nowadays, there are marketed CS-based formulations in nutraceutical and medical devices [ 44 , 78 ].…”
Section: Polymeric Nanocarriers Against Intracellular Infections: mentioning
confidence: 99%
“…Since then, the enthusiasm for researches on NO has almost reached the peak, and it has been increasingly valued in biology and medicine. To sum up, the roles played by endogenous NO in the human body are as follows: (i) NO is an endothelium-derived relaxing factor that relaxes vascular smooth muscle and prevents platelet aggregation [22,23]; (ii) NO is a reverse messenger of nerve conduction and plays an important role in the process of learning and memorization [24,25]; (iii) when activated upon phagocytosis and stimulation, macrophages release NO as toxic molecules that kill foreign invading microorganisms and tumor cells [26,27,28,29]; (iv) as a free radical, NO can damage normal cells, which plays an important role in myocardial and brain ischemia–reperfusion injuries [30,31]; and (v) NO can regulate the inflammatory reaction and cell proliferation processes, which are key to the wound healing process [32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nitric oxide acts as an endogenous signaling molecule influencing host immune responses to protozoan parasites in a positive manner and promoting subsequent reduction of parasitic burden. It has been shown that systemically administered nanoparticles possess the capability to release nitric oxide at targeted sites within the body or intracellularly within macrophages [102, 105]. Given the beneficial effect of nitric oxide on protozoan disease progression, nitric oxide releasing functionalized nanoparticles present possible alternatives to traditional toxic front-line chemotherapeutic options.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of peritoneal macrophages with these nanoparticles decreased the number of T. cruzi infected cells and the average number of intracellular replicative amastigotes per infected cell. These results suggest that the S-nitroso-MSA-CS NPs are promising nanocarriers for the treatment of Chagas disease and can deliver nitric oxide intracellularly [102]. Ursolic acid loaded poly-ε-caprolactone nanoparticles have also been evaluated in vivo showing similar efficacy to BZN standard formulations [103].…”
Section: Nanospheresmentioning
confidence: 99%